The economic impact of investments in cassava research in Uganda - Bua, A.; Acola, G.; Adupa, R.L.; Otim-Nape, G.W.; Baguma, Yona K.; Sserunkuma, D.; Manyong, Victor M.; Coulibaly, O. (CAB International, 2007)
Cassava plays a major role in both household and national food security in Uganda. However, cassava production in Uganda has been threatened by cassava mosaic disease. The government has made concerted efforts to evaluate, multiply and distribute new cassava planting materials in most districts. The new varieties outperformed the local varieties and quickly replaced them. An economic assessment of this programme using the benefit-cost approach revealed that the internal rate of return for this investment was 167%. This high rate of return can be partially explained by lack of data on some costs incurred by other development partners. The success of this investment was due to the joint contribution of complementary organizations. The biggest lesson learned is that it is important to strengthen the linkages between the research programme and other government institutions especially training, marketing, infrastructure development and political institutions.